The use of extended reality technologies in sport perceptual-cognitive skill research: A systematic scoping review - Kittel, A.; Lindsay, R.; Le Noury, P.; Wilkins, L. (Sports Medicine - Open, 2024)
Background Extended Reality (XR) technologies, such as Virtual Reality (VR) and 360°VR are growing rapidly in the scientific literature and sporting practice. These have been used for a range of skills, particularly perceptual-cognitive skills. However, to our knowledge, there is no systematic scoping review on this topic identifying the current state of play of the research area by characteristics such as study type, technology type, or sport investigated, and such a review would help guide the future direction of this area. Therefore, this study aimed to systematically review the extent of XR technology in sport for assessing and training athletes` and officials` perceptual-cognitive skills.